2019
DOI: 10.1021/acsbiomaterials.9b00474
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Gas Delivery by Fluorinated Poly(Ethylene Glycol)@Graphene Oxide Carrier toward Pharmacotherapeutics

Abstract: In view of preparing effective nitric oxide gas carriers, a fluorinated poly(ethylene glycol) (F-PEG) was non-covalently conjugated with acid-treated graphene oxide (GO) to prepare the composite of F-PEG@GO. When the persistence of NO gas doped on GO and F-PEG@GO was investigated for 3 h, the conserved NO gas decreased from 49.00±7.06 to 2.17±1.36 nmol/mg carrier and from 58.51± 6.02 to 4.58±2.22 nmol/mg carrier, respectively. The adsorption of F-PEG on GO and the doping of NO on GO and F-PEG@GO were declarati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 45 publications
(83 reference statements)
1
25
0
Order By: Relevance
“…GO-PEG-Ag damaged the bacterial structure causing leakage of cytoplasmic components, decrease of metabolic activity, and the generation of ROS ( Figure 5D). Recently, Workie et al 65 delivered nitric oxide (NO) using fluorinated PEG@GO carrier and found more effective antibacterial activity for NO-conserved F-PEG@GO than NO-conserved GO. The hydrophobic perfluorocarbon moiety on F-PEG@GO conserved more NO than GO resulting in superior activity.…”
Section: Antibacterial Efficacymentioning
confidence: 99%
“…GO-PEG-Ag damaged the bacterial structure causing leakage of cytoplasmic components, decrease of metabolic activity, and the generation of ROS ( Figure 5D). Recently, Workie et al 65 delivered nitric oxide (NO) using fluorinated PEG@GO carrier and found more effective antibacterial activity for NO-conserved F-PEG@GO than NO-conserved GO. The hydrophobic perfluorocarbon moiety on F-PEG@GO conserved more NO than GO resulting in superior activity.…”
Section: Antibacterial Efficacymentioning
confidence: 99%
“…The generated gas was introduced into a vessel placing the gas carrier materials in a closed system, following the reaction of 3Cu + 8HNO 3 → 3Cu­(NO 3 ) 2 + 2NO + 4H 2 O. The quantitative determination of NO gas in the carrier materials at a given time after stopping the loading was achieved following the previously reported method by a Griess assay method . The obtained quantity indicates NO gas in the carrier at a certain time after being loaded.…”
Section: Methodsmentioning
confidence: 99%
“…Gram-negative Escherichia coli ( E. coli ) and Gram-positive Staphylococcus aureus ( S. aureus ) were the strains used for the antimicrobial test based on the standard agar disk-diffusion method . The suspension (100 μL) of bacteria grown in the agar medium (Luria–Bertani for E.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of NO therapy with 2D nanomaterials has been explored, which showed great potential for treating cancer in the clinic. [ 151,438,439 ]…”
Section: Nir‐ii Ptt For Cancermentioning
confidence: 99%